2010
DOI: 10.1007/s00299-010-0934-5
|View full text |Cite
|
Sign up to set email alerts
|

PR-1 gene family of grapevine: a uniquely duplicated PR-1 gene from a Vitis interspecific hybrid confers high level resistance to bacterial disease in transgenic tobacco

Abstract: A functional contribution of pathogenesis-related 1 (PR-1) proteins to host defense has been established. However, systematic investigation of the PR-1 gene family in grapevine (Vitis spp.) has not been conducted previously. Through mining genomic databases, we identified 21 PR-1 genes from the Vitis vinifera genome. Polypeptides encoded by putative PR-1 genes had a signal sequence of about 25 residues and a mature protein of 10.9-29 kDa in size. PR-1 mature proteins contained a highly conserved six-cysteine m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
41
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(44 citation statements)
references
References 36 publications
2
41
0
1
Order By: Relevance
“…Therefore, AMF can suppress or reduce plant pests and diseases through the induction of systemic resistance (Pozo and Azcon-Aguilar 2007;Pineda et al 2010;Jung et al 2012). Depending on the plant/pathogen/AMF interaction, MIR could be associated with systemic acquired resistance (SAR)-like priming of salicylic acid (SA)-dependent genes (Khaosaad et al 2007;Gallou et al 2011), but more often coincides with priming of jasmonic acid (JA)-dependent defenses, especially in grapevine (Li et al 2010;Hao et al 2012). In this case, MIR is thought to result from the active suppression of components in the SA-dependent defense pathway, causing systemic priming of JA-dependent defenses (Pozo and Azcon-Aguilar 2007).…”
Section: Protection Against Biotic Stressesmentioning
confidence: 99%
“…Therefore, AMF can suppress or reduce plant pests and diseases through the induction of systemic resistance (Pozo and Azcon-Aguilar 2007;Pineda et al 2010;Jung et al 2012). Depending on the plant/pathogen/AMF interaction, MIR could be associated with systemic acquired resistance (SAR)-like priming of salicylic acid (SA)-dependent genes (Khaosaad et al 2007;Gallou et al 2011), but more often coincides with priming of jasmonic acid (JA)-dependent defenses, especially in grapevine (Li et al 2010;Hao et al 2012). In this case, MIR is thought to result from the active suppression of components in the SA-dependent defense pathway, causing systemic priming of JA-dependent defenses (Pozo and Azcon-Aguilar 2007).…”
Section: Protection Against Biotic Stressesmentioning
confidence: 99%
“…PR1 genes were first discovered in tobacco (Nicotiana tabacum L.) (Antoniw et al 1980), then many PR1 genes were identified from many monocotyledonous and dicotyledonous plants (Mitsuhara et al 2008;Li et al 2011). Most PR1 proteins with molecular weights of 14~17 kD are alkaline.…”
Section: Introductionmentioning
confidence: 99%
“…Host-pathogen interactions involve complicated defences, generally, host plants express a wide range of resistance-related proteins in response to pathogen attacks, include pathogenesis-related (PR) enzymes [3]. A comprehensive understanding of the proteins induced by pathogens will help reveal the complex molecular mechanisms that mediate plant disease resistance and will aid the development of new strategies to increase disease resistance in some economically important crops.…”
Section: Introductionmentioning
confidence: 99%
“…More recently, the significance of resistance-related proteins has been reported for many plant-pathogen interactions [13, 14], and some intensive attempts have also been made to engineer resistance to apple disease. Several genes have been isolated that are related to apple disease resistance [3, 1518]. The functions of some PR enzymes, including chitinases, β-1,3-glucanases and peroxidases, which act directly against pathogens, were also confirmed by some assays [1517].…”
Section: Introductionmentioning
confidence: 99%